Development of Flashcard Learning Media to Build A Space Using Assembler Edu In Elementary Schools - Saftri S, Mur Ida; Ibrahim, Doni Septu Marsa; Mukti, Husnul (Journal of Social Science and Education Research, 2024)
Development of Learning Media Flashcard AR Build a space using Assemblr Edu in elementary school. Thesis, Elementary School Teacher Education Study Program, Faculty of Education (FIP), Hamzanwadi University. The purpose of this research is to develop AR flashcard  learning media to build a space using assemblr edu in elementary schools, as well as to determine the feasibility level of learning media by media experts and material experts.   This research is a type of research and development. The development of this learning media product uses the ADDIE development procedure which is simplified to the development stage, namely: analyze, design, and development. The instruments in this study are interviews and questionnaires, and observations are used as student analysis. The validation of the learning media involves four validators consisting of two expert lecturers and two teachers according to their backgrounds relevant to the field being studied. The data from the validation results were analyzed based on the calculation of  the Gregory index,  showing the media validity coefficient for media experts in the study of 1 with very valid criteria and for material experts in this study also showed a validity coefficient of 1. So it can be concluded that  the AR flashcard learning media  to build a space using assemblr edu meets the criteria of high validity and is very feasible to be used by teachers as a student medium to learn building space materials in elementary schools.